Changes in the trophic level of an Alpine lake, Jezero v Ledvici (NW Slovenia), induced by earthquakes and climate change - Darko OGRIN; Irena REJEC-BRANCELJ; David M. LIVINGSTONE; Peter APPLEBY; Andrea LAMI; Milijan ŠIŠKO; Anton BRANCELJ (Journal of Limnology, 2000)
Despite relatively high nutrient levels, the Slovenian Alpine lake Jezero v Ledvici (1824 m a.s.l.; max. depth 15 m) is oligotrophic, with high transparency and low chlorophyll concentrations (<1 μg l-1). Daily mean air temperatures at the lake are estimated to vary between –15.4 °C and +18.8 °C. Low air temperatures combined with the blocking of incident solar radiation by the local topography result in the lake being ice-covered for over six months of the year, suggesting that the effects of climate on the ecology of the lake may be mediated by the timing of the ice cover. Sediment cores taken in 1996 were dated by 210Pb and 137Cs and analysed for DW, LOI, cladoceran and diatom remains, pigments, C, N and S. A total of 50 diatom taxa and 4 cladoceran taxa were found. The base of the unsupported 210Pb record at 17.4 cm was dated to 1825 AD ± 25 y. An abrupt change in DW and LOI was observed at a depth of 17 cm, coinciding with a change in the cladoceran community and in C and N concentrations. From a depth of 12 cm (83 ± 4 y BP) upward, a sharp change in S and plant pigment concentrations were recorded, followed by an increase in diatom abundance at a depth of about 10 cm (63 ± 4 y BP). The timing of quantitative changes in the physical and chemical properties of the sediment, and in the community structure of diatoms and Cladocera, coincides with the occurrence of three earthquakes in the 19th century. Changes in the diatom and cladoceran record were compared with a tree-ring width index based on Larix decidua from the shore of the lake over the last 136 years, and with reconstructed air temperatures from 1781 – 1996. With a 4-y lag, a weak positive correlation exists between the tree-ring width index and the air temperatures. Although diatom abundance generally shows no correlation with the tree-ring width index, a negative correlation was found in the case of Fragilaria pinnata and Amphora lybica, interrupted only between 1942 and 1955. A similar pattern to this latter was also observed in the case of the Cladocera. During the last 250 y, anthropogenic influence on the lake catchment area has been confined mainly to limited sheep grazing. The main cause of changes occurring in the lake itself is likely to be eutrophication resulting from the input of allochthonous material from landslides triggered by earthquakes. During the last three decades, however, the main factor influencing biotic change appears to have been the increase in mean air temperature, possibly acting via ice cover.